Stimuli-reponsive polymer composite for energy saving thermotropic smart window - Lee, Heng Yeong (2018)
Transparent glasses are hotly pursued as premium construction materials in transport vehicles and architectural buildings for its aesthetic appeal. Due to widespread usage of transparent glasses, 43% of global world primary energy are spent on heating, ventilation and air-conditioning in buildings. Moreover, individual can also experience uncomfortable situations, such as glaring sunlight, skin and thermal discomfort.